Analysis Of 30 Minute Circuit Training And Walking Exercises Results On Body Components - Gigih Siantoro; Destha Rizky Ramadhani; Okta Ardiansyah; Tesya Fitria Permatasari; Marsya Dwi Khoirunisa; Ach. Faidir Rahman; Ahmad Riyan Sabela; Bayu Agung Pramono (Indonesian Journal of Kinanthropology (IJOK), 2024)
Background: This study aims to determine the effectiveness of reducing weight, BMI and fat with fun exercise through circuit training. Methods: This research uses a quantitative approach method. This research was conducted at Surabaya State University on March 15 2024 - April 5 2024. 20 students with an average age of 18 - 20 years participated in this research, they were divided into 2 groups, namely 10 students in the circuit training treatment group and 10 students in the circuit training treatment group. 30 minute walking treatment. Training is carried out within 3 weeks carried out 4 times a week. They carry out physical activity in the form of aerobic exercise which consists of exercise stations, namely between 8-16 exercise stations. The exercise is done by moving from post one to post two until the last post. Body composition was carried out using the Tanita scale measuring instrument version BC-545N. The urgency of this research was carried out because there are many teenagers who are obese in Indonesia. Results: The results of this research were that circuit training, which was carried out 4 times a week, and carried out for 3 weeks, was successful in reducing weight, BMI, and FAT. Conclusions: In conclusion, circuit training and walking for 30 minutes has an effect on reducing body weight, BMI and FAT